Enhancing English Language Learning Through the Cooperative Learning Method: A Study Among Communication Studies Students at UMI - Andi Hudriati; Rahmat Rahmat; Husnul Mujaddidah (Tamaddun Life, 2024)
This Classroom Action Research (CAR) investigated the effectiveness of cooperative learning in enhancing student motivation and academic performance in an English course for first-semester Communication Studies students at the Faculty of Letters, Universitas Muslim Indonesia (UMI). A total of 25 students participated in two iterative cycles, each comprising planning, implementation, observation, and reflection. Data were collected through observation sheets that tracked classroom activities and assignments designed to evaluate improvements in listening, speaking, reading, and writing skills. The results from Cycle 1 showed a moderate increase in student engagement, from 67% to 78%, but did not meet the predetermined mastery criterion (average score of 72, below the minimum of 75). In contrast, Cycle 2 revealed a marked improvement, with engagement levels rising from 84% to 90%, and the average score increasing to 86. Observational data indicated that shifting to a student-centered classroom environment and regulating mobile phone use for academic purposes boosted students’ confidence and collaboration. Students also demonstrated enhanced comprehension and fluency, aligning with broader findings in cooperative learning literature. Overall, these findings underscore the potential of cooperative learning to address the limitations of conventional lecture-based instruction. By engaging students in structured group activities, fostering peer support, and offering consistent feedback, cooperative learning can significantly improve motivation and learning outcomes. The success of this approach suggests that it may be beneficial for adoption in other higher education contexts seeking to elevate student participation and language proficiency.